In vitro anti-leukemic activity of Terminalia arjuna bark extract loaded chitosan nanoparticles on HL-60 cell lines - Murukadas, Gokul; George, Anju Rani; V S, Hansiya; Sajeev, Sradha; Thangasamy, Kavimani; Jeganathan, Aarthi; Byju, Anju; Geetha, Natesan (Asia-Pacific Journal of Science and Technology, 2025)
The bark of Terminalia arjuna (Roxb. ex DC.) Wight & Arn. has been traditionally used in Indian medicine for treating various ailments, including leukemia. Chitosan, a natural biopolymer, serves as a promising carrier for targeted drug delivery. This study focuses on the encapsulation of hexane-ethanolic bark extract (HEB) of T. arjuna using chitosan nanoparticles (CSNPs) and evaluates their anti-leukemic potential against HL-60 cell lines. The HEB-loaded CSNPs (HEB-CSNPs) were synthesized and their entrapment efficiency, drug release profile and cytotoxic activity were assessed. In vitro release studies demonstrated a controlled and sustained drug release of 96.66% within three hours. Drug release kinetics followed the Higuchi model with a correlation coefficient (R²) of 0.98, indicating diffusion-controlled release. Fourier transform infrared (FTIR) spectra confirmed the presence of characteristic functional groups of both chitosan and the plant extract. X-ray diffractometer (XRD) analysis revealed an increase in nanoparticle size from 56.88 nm (control) to 64.53 nm upon encapsulation. Search engine marketing (SEM) imaging showed well-dispersed nanoparticles with a large surface area. Cytotoxicity analysis on HL-60 cells demonstrated dose-dependent activity, with an inhibitory concentration (IC) IC50 value of 185.2 μg/mL for HEB-CSNPs. Conclusion: Overall, this study demonstrates that CSNPs are effective carriers for T. arjuna bark extract, ensuring efficient encapsulation, sustained release, and significant anti-leukemic activity in vitro. These findings suggest the potential of HEB-CSNPs as a biocompatible and eco-friendly nanomedicine for leukemia treatment and warrant further investigation in preclinical models.